عناية المغاربة بالسيرة النبوية (كتاب الشمائل أنموذجًا): Moroccan People's Attention to the Prophet's Sirah (Study of the Kitab of al-Syama’il al-Muhammadiyyah) - Murad Zahwi (البصيرة: مجلة الدراسات الإسلامية, 2022)
This study aims to find out how the Moroccan community pays attention to the sirah nabawiyyah, specifically in the book of al-Syamā'il al-Muḥammadiyyah. This study uses a qualitative method with a descriptive analytical and historical approach. The results showed that among the forms of Moroccan people's attention to the sirah of the Prophet Muhammad especially the book of al-Syamā'il al-Muḥammadiyyah is the number of syurūḥ (explanations) of the Moroccans to the book of al-Syamā'il al-Muḥammadiyyah as evidence of their attention to the book. The book of al-Syamā'il al-Muḥammadiyyah by al-Tirmiżī is one of the most important references to get to know the figure of the Prophet because it has contained everything related to his character, character and physical. Al-Tirmiżī strongly maintains the validity of the hadith and is committed to the validity of the hadith he narrates